ANATOMICAL COMPARISON OF THE SPINAL NERVOUS SYSTEM - Kumar, Chandan (International Journal of Multidisciplinary Research and Studies, 2020)
The fundamental anatomical characteristics of the autonomic nervous systems of animals that are not mammalian in origin. In addition to this, it makes an attempt to describe the parallels between the autonomic nervous systems of fish and tetrapods, as well as the increasing complexity of the latter. The extraordinary resemblance that exists between the many classes of vertebrates, with the probable exception of the cyclostomes, is one of the most distinctive characteristics of the autonomic nervous systems of vertebrates. An increase in system complexity can be observed, as elasmobranchs have segmental ganglia that are only partially connected longitudinally, whereas teleost fish and tetrapods have well-developed paired sympathetic chains in their nervous systems. This indicates that the complexity of the system has evolved over time. Some groups' sympathetic chains may be shorter than others (dipnoans and caecilians, for example), and sympathetic chains in snakes have not been adequately documented. Cranial autonomic pathways are present in the oculomotor (III) and vagus (X) nerves of gnathostome fish and the tetrapods, and with the evolution of salivary and lachrymal glands in the tetrapods, also in the facial (VII) and glossopharyngeal (IX) nerves. Cranial autonomic pathways are present in the facial (VII) and glossopharyngeal.